Réponses

  • Utilisateur Brainly
2014-09-28T13:25:47+02:00
5x = 0
x = 0/5
x = 0

(- 2x - 5)(3x + 2) = 0
- 2x - 5 = 0
2x = - 5
x = - 5/2

ou

3x + 2 = 0
3x = - 2
x = - 2/3
Rhalala quelle vitesse
Héhé ! :)
Merci ;)
De rien, n'oublie pas de voter pour la "meilleure réponse" ! :)
2014-09-28T13:26:01+02:00
5x = 0
x =05
x =0

(-2x-5)(3x+2)=0

-2x-5 = 0                             3x+2 =0
-2x = 5                                 3x = -2
x =  -5/2                                 x = -2/3

donc solution  s =( -5/2 ; -2/3)